On-demand, readily degradable Poly-2,3-dihydrofuran enabled by anion-binding catalytic copolymerization - Zhen Zhang; Wenxiu Lv; Maosheng Li; Yanchao Wang; Xianhong Wang; Youhua Tao (Nature Communications)
Abstract Copolymerization with cleavable comonomers is a versatile approach to generate vinyl polymer with viable end-of-life options such as biodegradability. Nevertheless, such a strategy is ineffective in producing readily degradable 2, 3-dihydrofuran (DHF) copolymer with high-molecular-weight (>200 kDa). The latter is a strong and biorenewable thermoplastic that eluded efficient cationic copolymerization synthesis. Here, we show that an anion-binding catalyst seleno-cyclodiphosph(V)azanes enable the efficient cationic copolymerization with cyclic acetals by reversibly activating both different dormant species to achieve both high living chain-end retention and high-molecular-weight. This method leads to incorporating low density of individual in-chain acetal sequences in PDHF chains with high-molecular-weight (up to 314 kDa), imparting on-demand hydrolytic degradability while without sacrificing the thermomechanical, optical, and barrier properties of the native material. The proposed approach can be easily adapted to existing cationic polymerization to synthesize readily degradable polymers with tailored properties while addressing environmental sustainability requirements.